2013
DOI: 10.2174/0929867311320210003
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids in Atherosclerosis: An Overview of Their Mechanisms of Action

Abstract: Polyphenols are composed of a wide variety of molecules that are classified into several categories, according to their chemical type such as phenolic acids, flavonoids, stilbenes, and lignans. Many studies have proven the beneficial effects of flavonoids in atherosclerosis progression and cardiovascular disease. Dietary flavonoids reduce oxidative stress and exert anti-inflammatory actions. Moreover, flavonoids have the ability to avoid the thrombus formation, improve endothelial function, modify lipid levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(65 citation statements)
references
References 0 publications
1
61
0
3
Order By: Relevance
“…Examples of some of the most widely studied flavonoids are quercetin (present in onions as well as most citrus fruits and berries), catechins (from green tea and cocoa/ dark chocolate), and luteolin (in broccoli, olive oil, and Phytochemicals and Adaptive Responses green peppers). As reviewed elsewhere, these and other flavonoids have demonstrated therapeutic effects in experimental models of cancer (Romagnolo and Selmin, 2012) and cardiovascular disease (Siasos et al, 2013). There are numerous examples of neuroprotective/ therapeutic effects of flavonoids in various cell culture and animal models of neurodegenerative disorders.…”
Section: A Oxidative Stressmentioning
confidence: 99%
“…Examples of some of the most widely studied flavonoids are quercetin (present in onions as well as most citrus fruits and berries), catechins (from green tea and cocoa/ dark chocolate), and luteolin (in broccoli, olive oil, and Phytochemicals and Adaptive Responses green peppers). As reviewed elsewhere, these and other flavonoids have demonstrated therapeutic effects in experimental models of cancer (Romagnolo and Selmin, 2012) and cardiovascular disease (Siasos et al, 2013). There are numerous examples of neuroprotective/ therapeutic effects of flavonoids in various cell culture and animal models of neurodegenerative disorders.…”
Section: A Oxidative Stressmentioning
confidence: 99%
“…Long-term consumption of a polyphenol-rich diet is associated with a reduction of cardio-vascular (CVD) risk, according to the literature [11,12]. This study aimed to assess the effects of prolonged in vitro exposure to quercetin and EGCG (exposure time of 24 and 48 h, respectively) on the membrane anisotropy and transmembrane potential of PBMCs isolated from NC subjects and HC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some flavonoids (e.g., the soy isoflavone subgroup) induce significant effects on erythrocyte membrane fluidity and deformability, affect the cellular mechanics and cause some endocrine perturbations [9,10]. Epidemiological studies have also revealed that a flavonoid-rich diet correlates with increased longevity and decreased incidence of cardiovascular diseases [3,[11][12][13][14]. Polyphenol-rich diets are documented to reduce the incidence of atherosclerotic lesions.…”
Section: Introductionmentioning
confidence: 99%
“…This class of phytochemicals possesses various biological functions such as anti-cancer, anti-proliferative, antioxidant, pro-apoptotic, anti-inflammatory, and neuroprotective activities (You et al, 1998;Manosroi et al, 2005;Jiang et al, 2013;Zhu et al, 2013;Tan et al, 2014). Casticin (3', 5-dihydroxy-3, 4', 6, 7-tetramethoxyflavone) is one of the bioactive flavonoids obtained from polyphenol plants, which are composed of a wide variety of molecules that are classified into several categories, according to their chemical type, such as phenolic acids, flavonoids, stilbenes, and lignans (Siasos et al, 2013 ). Casticin is a main active compound in roots, aerial parts, seed, wood, stems, leaves and fruits of variety of plants ( Figure 1 and Table 1), has been reported to be responsible for a wide spectrum of biological and pharmacological activities including immunomodulatory (Mesaik et al, 2009;Ling et al, 2012), anti-hyperprolactinemia (Hu et al, 2007b;Ye et al, 2010), anti-tumor (Haidara et al, 2006;Shen et al, 2009;Ling et al, 2012;Zeng et al, 2012), neuroprotetective (Ling et al, 2012), anti-inflammatory (Lin et al, 2007b;Choudhary et al, 2009;Velpandian et al, 2013) and analgesic activities (Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%